Origin of the Adis: A Polemical Discourse Authors - Abang Pertin (Dera Natung Government College Research Journal)
In tribal worldview, the conception of origin and migratory legends often stems from mythological nuances. The similar case is also evidently traced and pursued in context of the Adis residing in central belt of Arunachal Pradesh. Hence, this paper attempts to reflect the idea of Adi origin and migration from the existing domains of arbitrary stances in discursive way. Also, it trysts to extrapolate the juxtaposing constructs of both mythical and methodical parameters in scholastic approach.